Hypertension outcomes and cardiovascular status in young adults with childhood-diagnosed white coat hypertension - Westerståhl, Maria; Wühl, Elke (Archives of disease in childhood, 2017)
White coat hypertension (WCH) describes untreated subjects displaying elevated blood pressure (BP) in the clinical setting as opposed to normal ambulatory BP monitoring (ABPM) or BP taken at home.1 Adults with WCH are more likely to progress to sustained hypertension (SH) and to be at increased cardiovascular risk compared with normotensive subjects.2 Since it is unknown whether children with WCH progress to SH,3 we sought to determine hypertension outcomes using ABPM and cardiovascular status in young adults with childhood-diagnosed WCH. In a previous study conducted in Swedish healthy schoolchildren, we identified 56 (3.8%) out of 1470 participants as having WCH, which was defined as systolic and/or diastolic casual BP >95th distribution adjusted height-related and sex-related percentile in three separate visits, but …